Analysis of Short Term Funding with Mudharabah Agreements in Bank Syariah Indonesia (Study on Indonesian Sharia Bank KC Jambi Gatot Subroto) - Anggraini, Dian Septi; Siregar, Erwin Saputra; Yulistiani, Yulistiani; Mellyani, Netty Purnama Sari; Rusmiyati, Melly; Assaidiqi, M. Irfan; Nazori, Nazori (PT Inovasi Pratama Internasional, 2024)
This research discusses the Analysis of Short-Term Funding with Mudharabah Agreements at Indonesian Sharia Banks (Study at the Jambi Gatot Subroto Branch Office Sharia Bank). The aim of this research is to describe the causes of the decline in the level of mudharabah financing in 2020 and the reasons why short-term funding in mudharbah contracts is less banking friendly due to the complexity and many requirements for MSMEs. This research is field research using descriptive qualitative methods. Data collection involves observation, interviews and documentation. Test the validity of this research using triangulation techniques. The subjects in this research were Bank Syariah Indonesia Jambi Gatot Subroto Branch Office. The results of this research show that there are two factors causing the decline in mudharabah financing in 2020, namely internal and external factors, internal factors include ineffective risk management, inefficient operational management, and declining service quality. External factors include the COVID-19 pandemic and the unreliability of customers in mudhrabah financing. The factors that cause short-term funding at Bank Syariah Indonesia Jambi Gatot Subroto Branch Office to be less banking friendly towards MSMEs are internal factors including fairly strict risk policies, complicated requirements, and a lack of understanding about MSMEs. External factors include a lack of support infrastructure such as providing business training with short-term funding.